Critical Risk Factors of PPP Water Supply Project in Indonesia (Case Study: West Semarang Drinking Water Supply Project) - Parlindungan, David Raymond; Setiadi, Rukuh; López, Marcela (Department of Urban and Regional Planning, Universitas Diponegoro, 2022)
The increasing need for water cannot be denied, given the growing population and standard of living. Therefore, the Government seeks to involve the private sector through the Public-Private Partnership (PPP) scheme in the West Semarang Drinking Water System project to overcome the cost of providing a significant investment. In 2012 the West Semarang Drinking Water Supply Project (WS-DWSS) was developed by the Government. But in 2015, the project was stopped due to changes in the Law of the Republic of Indonesia Number 7 of 2004 concerning Water Resources. PPP schemes in the water sector are relatively new in Indonesia and often face many challenges in their implementation. Through the lens of a theoretical framework and by taking a qualitative and quantitative approach based on primary and secondary data, this thesis assesses the critical risk factors during project implementation in the perception of the public and private sectors. This thesis shows that the both sectors agree that there are 3 most critical risks for drinking water projects: availability of raw water (continuity/quantity), natural disasters, tariff setting & demand projection error. However, the two sectors also have different perceptions of critical risk factors. This difference shows that the two sectors have distinct views and goals as part of a collaborative project. By knowing the similarities and differences, mitigation efforts can be made to minimize the risk of drinking water projects with the PPP scheme.